(untitled) (Scientia Agricola, 2015)
In recent years, there has been an increase in interest in super high-density (SHD) olive (Olea europaea L.) groves because they offer early entry into production, increased productivity and the possibility of using modified mechanical vine harvesters. This study was carried out in a young SHD olive grove to examine vegetative, histo-anatomical and productive characteristics and oil quality of the Spanish Arbequina and Italian Maurino and Leccino cultivars, characterized by low, low-to-medium and high vigor, respectively. Arbequina had low vigor and limited development in height and width, as well as a high leaf/wood ratio. Maurino had a canopy volume similar to that of Arbequina and, despite a great tendency to grow in height, had low vigor, a rather compact vegetative habitus, but good lighting in the canopy and high production efficiency. In Maurino, a greater palisade parenchyma height and a larger exposed lateral surface area of the palisade parenchyma cells were observed. In the fourth year after planting, fruit production of Arbequina was about 30 % less than Leccino and Maurino. The oil content on a dry weight basis was slightly higher in Arbequina and Maurino than in Leccino. Oil quality was good for all cultivars.